ANALISIS ANTESEDEN LOYALITAS PELANGGAN OPERATOR TELEPON SELULER - Suyitno, Dipa Nugraha (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
This research is aimed to analyze the influence of antecedent factors onto Esia Customer Loyalty in Solo. Data was obtained from 123 people via questionnaire by convenience sampling. The analysis results show that: perceived service quality affects customer loyalty positively, perceived service quality affects trust in the provider positively, perceived service quality affects corporate image positively, trust in the provider affects customer loyalty positively, corporate image affects customer loyalty positively, the effect of perceived service quality is greater by indirect effect through corporate image and or trust in the provider. Its direct effect is marked by ï¢ 0.172 while its indirect effect through corporate image is marked by ï¢ 0.184 and through trust in the provider is marked by ï¢ 0.175.